Мaintenance of quality of mineral oils at stages from life cycle - Дровнін, С.С.; Демидко, В.Г.; Пашинський, А.Й. (Proceedings of National Aviation University (archive), 2004)
The mechanism mass change in system «gas–coalhydrargium a liquid» is considered. The mathematical model mass change off water of mineral oils is developed. The dependence which is taking into account design feature of barbotage of devices, Physics -chemical properties of a liquid and gas is received. The parameters and sufficient conditions of modes of processing of mineral oils by inert gases are determined. The application mass change of a method of processing of mineral oils for preservation of properties at stages of their life cycle is proved.